Performance, nutrient digestibility and carcass characteristics of rabbit fed sweet potato based diets (1999)
The performance, nutrient digestibility and carcass characteristics of rabbits fed dehydrated sweet potato tops and sweet potato root meal in proportions of 100: 0. 90 : 10, 80: 20. 70 : 30, 60 : 40 and 50: 50 were investigated. There was no significant difference (P>0.05) in daily feed intake. However, rabbits fed diets in proportion of 80 : 20 (T.) recorded the highest daily weight gain and was significantly different (P<0.05) from other dietary treatments. No significant difference (P>0.05) was reported for the apparent digestibility of crude fibre and ash. Rabbits on diets T3 (80 : 20) and T4 (70 : 30) had the highest killing out per cent and head weights. No mortality was recorded throughout the duration of this study.